Effects of hypercaloric enteral intervention on malnutrition patients with a history of febrile seizure before the age of six - Sünnetçi Silistre, Eda; Özpenpe, Özlem; Hatipoğlu, Halil Uğur; Doğan, Ali; Ozdener, Fatih (Journal of Surgery and Medicine, 2020)
Aim: Febrile seizure is the most prevalent ( 5%) convulsion in children between 3 to 60 months of age and has been related to iron deficiency. Thus, when it is combined with malnutrition, it may increase negative outcomes. In this study, we present the effects of hypercaloric (1.5 kcal mL-1) nutritional intervention on undernourished children with a history of febrile convulsions prior to the age of 6. Methods: A cohort of 44 patients between ages 1-6 years with a history of a febrile seizure was included in the study. Hypercaloric nutritional intervention was applied to all patients. Baseline patient records containing anthropometrical and micronutrient measurements were compared with the 3rd month and the 6th month visits. All patient records were retrospectively obtained from Istanbul Research and Training Hospital, İstanbul, Turkey. Results: There were significant improvements in the z-scores of weight (P=0.002) and body mass index (P<0.001). Approximately 50% of iron and 25-hydroxyvitamin D3 (25D3) deficient patients were cured and their serum concentrations increased significantly (P<0.001 for both). Treatment did not affect iron concentrations in patients without iron deficiency (P=0.074). Normal concentrations of 25D3, folate, and vitamin B12 improved inside the optimal micronutrient ranges without toxicity. Conclusion: Overall, hypercaloric nutritional intervention abated iron and 25D3 deficiency and significantly improved the z-scores of BMI and weight in malnourished pediatric patients under the age of 6 with a history of febrile seizures without toxicity.